On the Stability of Mixed Oligopoly Equilibria with CSR Firms - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper examines the stability conditions of the equilibria in a market where profit-maximizing and CSR firms coexist in the presence of an environmental externality. An equilibrium in mixed duopoly is stable for low impact of productivity on pollution and high CSR sensitivity to consumer surplus. In addition, a mixed oligopoly equilibrium is stable if the number of CSR is sufficiently low.
Keywords: H23; L13; O31; 330